Analisis reformulasi serbuk kopi fungsional tinggi serat berbasis inulin dan maltodekstrin rintang terhadap stabilitas fisikokimia - Agustine, Nanda; Suarti, Budi; Alias, Suhaimi (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
The reformulation of high-fiber functional coffee powder using inulin and resistant maltodextrin represents an effort to enhance product functionality while maintaining physicochemical stability. This study aimed to analyze the effect of inulin and resistant maltodextrin incorporation on the physicochemical stability of functional coffee powder. A Completely Randomized Design (CRD) was applied with five treatments: control (without fiber), resistant maltodextrin at 12.4% and 20%, and inulin at 12.4% and 20%, each with three replications. The parameters evaluated included pH, °Brix, moisture content, water activity (aw), color, viscosity, solubility, and particle size. The results showed that fiber addition significantly affected °Brix (12.0–12.9), moisture content (8.32–10.05%), water activity (0.50–0.55), viscosity (118.2–127.5 cP), color, and particle size (1430–1630 µm), while no significant effect was observed on pH (6.50–6.63) (p>0.05). Overall, the reformulation with resistant maltodextrin at 12.4% demonstrated the most sTabel physicochemical characteristics. These findings indicate that inulin and resistant maltodextrin can be effectively utilized to develop high-fiber functional coffee powder with accepTable physicochemical stability.